Uniform stress distribution road piezoelectric generator with free-fixed-end type central strike mechanism. (15th January 2022) - Hong, Seong Do; Ahn, Jung Hwan; Kim, Kyung-Bum; Kim, Jeong Hun; Cho, Jae Yong; Woo, Min Sik; Song, Yewon; Hwang, Wonseop; Jeon, Deok Hwan; Kim, Jihoon; Jeong, Se Yeong; Woo, Sang Bum; et al.
Abstract: A self-powered energy harvester for real roads to predict and detect black ice formation and pinpoint dangerous road sections was developed. An open-type piezoelectric device was developed for a high-efficiency module to achieve uniform stress distribution for enhanced energy harvesting performance by free-fixed-end type central strike mechanism. The output performance of the open-type device was 80% higher than that of the closed-type device. A uniform stress distribution road piezoelectric generator (URPG) with 120 open-type devices was installed on real roads. The URPG showed output power performance of up to 2.38 mW/cm 3 when a vehicle passed once under the condition of being buried 2.5 cm below the road surface. The URPG can operate a wireless temperature sensor monitoring system for 83 s and charge a cellphone battery for 53 s. The developed self-powered energy harvesters can be used to reduce accidents caused by black ice on real roads. Highlights: We developed self-powered energy harvesters for real roads. The goal was to detect black ice formation and find dangerous road sections. We developed an open-type piezoelectric device for a high-efficiency module. A uniform stress distribution road piezoelectric generator (URPG) was installed. The URPG can operate a wireless temperature sensor and charge a cellphone.